Development and validation of doctoral student social support perception scale - Yang, Xiaohan; Yeo, Kee Jiar; Lee, Shih-Hui; Wong, Boon Yew; Handayani, Lina (Institute of Advanced Engineering and Science, 2025)
The perception of social support is crucial for doctoral students' academic careers, yet there is a notable absence of scales specifically designed to measure the social support that doctoral students receive. Consequently, there is a clear need for an effective tool to assess the level and nature of support perceived by these students. The Doctoral Students Social Support Perception Scale (DSSPS) is a multidimensional instrument developed to evaluate social support received by doctoral students from supervisors, family, and peers/friends. This scale operates in two phases: the first phase uses exploratory factor analysis to identify three potential dimensions of perceived social support: resource provision, emotional inspiration, and appropriate attention. The second phase employs confirmatory factor analysis to demonstrate the scale's robust overall fit. The results also indicate high internal consistency as well as convergent and discriminant validity. These findings suggest that the DSSPS is both an effective and reliable measure to assess the extent and nature of social support perceived by doctoral students.